Corporate Environmental Responsibility at Every Stage of Mining Business According to Undang-Undang Nomor 4 Tahun 2009 tentang Pertambangan Mineral dan Batubara - Rama Wibawa (Politeknik Siber Cerdika Internasional, 2026)
Background: Mining sector plays an important role in the Indonesian economy, it also poses significant risks to environmental sustainability. The main legal issue concerns the inadequacy of enforcement mechanisms under Law No. 4 of 2009 concerning Mineral and Coal Mining, which involves weaknesses in corporate liability for environmental obligations at every stage of mining activities, from exploration to post-mining reclamation. Objective: This study aims to explain the importance of corporate responsibility in ensuring that mining business activities are carried out in accordance with environmental protection principles and relevant laws and regulations. Methods: This study refers to the provisions of Law No. 4 of 2009 of the Republic of Indonesia concerning Mineral and Coal Mining, particularly those governing the stages of mining activities, including exploration, production operations, and post-mining activities. The study uses a normative legal approach. Result: There is a gap in law enforcement under the Mineral and Coal Mining Law and its implementing regulations. Environmental assessment requirements remain largely formalistic, monitoring remains ineffective, approximately 40% of Mining Business Permit (Izin Usaha Pertambangan or IUP) holders do not comply with legal obligations, and criminal sanctions are rarely applied as a primary enforcement measure. The clear link between corporate environmental responsibility and criminal liability under the 2023 National Criminal Code has not been fully utilized. Conclusion: To strengthen corporate environmental responsibility in mining, effective reforms of the Environmental Impact Assessment (Analisis Mengenai Dampak Lingkungan or AMDAL) system are needed to reduce chronic non-compliance, improve compliance with reclamation and post-mining safeguards.